BIOLOGY, EPIDEMIOLOGY, GENETIC CHARACTERISTICS, AND RESEARCH PRIORITIES OF WEST NILE VIRUS - Bissenbay , A.O.; Zhigailov , A.V.; Neupokoyeva , A.S.; Naizabayeva, D.A.; Skiba, Y.A.; Dmitrovskiy, A.M.; Shapiyeva, Zh.Zh. (Eurasian Journal of Applied Biotechnology, 2019)
West Nile fever (WNF) is an acute viral, natural foci infectious disease with a zoonotic mechanism of transmission. WNF has a high incidence in countries with a temperate climate in the summer-fall season. The causative agent is West Nile virus (WNV), which belongs to the Flavivirus genus of the Flaviviridae family. WNV was first isolated in the West Nile district of Uganda in 1937 from the blood of a native Ugandan woman. Several sporadic cases were then reported in Israel, Egypt, India, France, and South Africa from the 1950s to 1980s. However, WNV became a global public health concern after introduction of the virus in New York in 1999, which consequently led to its massive spillover across almost all of the United States, Canada, and Central America. In the 1990s, several significant outbreaks of WNF also occurred in Russia. The virus currently circulates in almost all countries of the African continent, Asia (mainly on the Hindustan subcontinent), Israel, and Europe. In Kazakhstan, WNF cases have mainly been reported in territories bordering Russia and in some areas of the Turkestan oblast. Birds serve as amplifier hosts, and mosquitoes, mainly of the genus Culex, are the primary vectors. Human and horses are the dead-end hosts of the virus. The clinical manifestations of WNV infection in humans range from asymptomatic illness to encephalitis, leading to various neurodegenerative diseases. This article reviews current data on the biology, epidemiology, ecology, geographical distribution, virology, pathology, structure, and genome characteristics of WNV, as well as the main laboratory diagnosis methods and further research priorities.